East Java Province GRDP Projection Model Using Night-Time Light Imagery - Firman Afrianto (East Java Economic Journal, 2022)
Economic growth, regional development, and human activities are some of the things that are very strongly related and influence each other. Approaches to forecasting the growth of the three are mostly carried out using both conventional and non-conventional data. Utilization of Nighttime Light Imagery satellite imagery is included in a non-conventional approach to forecasting Gross Regional Domestic Product. This study applies the use of satellite imagery to predict the regional development of East Java Province, to find patterns of agglomeration and the formation of clusters of economic development in the future.